2003
DOI: 10.1007/s00125-003-1034-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gemfibrozil, itraconazole, and their combination on the pharmacokinetics and pharmacodynamics of repaglinide: potentially hazardous interaction between gemfibrozil and repaglinide

Abstract: Aims/hypothesis. Our aim was to investigate possible interactions of gemfibrozil, itraconazole, and their combination with repaglinide. Methods. In a randomised crossover study, 12 healthy volunteers received twice daily for 3 days either 600 mg gemfibrozil, 100 mg itraconazole (first dose 200 mg), both gemfibrozil and itraconazole, or placebo. On day 3 they ingested a 0.25 mg dose of repaglinide. Plasma drug and blood glucose concentrations were followed for 7 h and serum insulin and C-peptide concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
266
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(281 citation statements)
references
References 11 publications
12
266
0
3
Order By: Relevance
“…In vivo, gemfibrozil increases the total exposure of repaglinide eightfold. 21 Several reports of severe, prolonged hypoglycemia have been documented with the combination. 22 Strong inhibitors of CYP3A4, such as azole antifungal agents and erythromycin derivatives, may also enhance the hypoglycemic effect of repaglinide.…”
Section: Pharmacy Updatementioning
confidence: 99%
“…In vivo, gemfibrozil increases the total exposure of repaglinide eightfold. 21 Several reports of severe, prolonged hypoglycemia have been documented with the combination. 22 Strong inhibitors of CYP3A4, such as azole antifungal agents and erythromycin derivatives, may also enhance the hypoglycemic effect of repaglinide.…”
Section: Pharmacy Updatementioning
confidence: 99%
“…It is mainly metabolized via N-methylation and para-hydroxylation by CYP2C8 through phase I metabolism, and to a lesser extent by CYP2C9 (Baldwin et al, 1999). Recently, the contributions made by CYP2C8 to the metabolisms of cerivastatin, paclitaxel, repaglinide, and verapamil have been studied Tracy et al, 1999;Mück, 2000;Niemi et al, 2003a). The pharmacokinetics of rosiglitazone is known to be altered when it is co-administered with other drugs which were involved with the induction or inhibition of CYP2C8, such as, gemfibrozil, trimethoprim and rifampin (Tracy et al, 1999;Park et al, 2004;Hruska et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with a report by Niemi et al (2001) showing that clarithromycin, a CYP3A4 inhibitor, signifi cantly increased the AUC 0−∞ and C max of repaglinide. Niemi et al (2003) reported that gemfi brozil signifi cantly increased the AUC 0−∞ of repaglinide 8.1-fold, while Kajosaari et al (2005) also reported that co-administration of repaglinide with the known P-gp inhibitor cyclosporine A signifi cantly increased the plasma concentration of repaglinide in humans.…”
Section: Discussionmentioning
confidence: 99%